Proceedings of the 2017 International Technical Meeting of the Institute of Navigation 2017
DOI: 10.33012/2017.14915
|View full text |Cite
|
Sign up to set email alerts
|

Long Baseline GPS+BDS RTK Positioning with Partial Ambiguity Resolution

Abstract: Reliable real-time kinematic positioning requires the occurrence of incorrect integer ambiguity estimates to be limited to a maximum tolerable rate. For long baselines this usually implies long convergence times due to the presence of atmospheric delay parameters. Several simulation studies have shown that partial ambiguity resolution (PAR) techniques are beneficial in terms of faster solutions, since it is more likely that a subset of all ambiguities can be reliably resolved rather than the full set, but they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…where d is the baseline between two receivers (km). It should be noted that the baseline should not encounter the tropospheric delay gradients or nonlinear effects in the ionosphere (Brack, ), which typically more than about 50 km.…”
Section: Methodsmentioning
confidence: 99%
“…where d is the baseline between two receivers (km). It should be noted that the baseline should not encounter the tropospheric delay gradients or nonlinear effects in the ionosphere (Brack, ), which typically more than about 50 km.…”
Section: Methodsmentioning
confidence: 99%
“…8.1.1.6], we consider 6 BSs in the simulation. We also set the interval between two consecutive measurement reports to 100 milliseconds [59]- [61], and the number of measurements used to resolve the integer ambiguity to 50 [61]. Each simulation result is the average of 2,000 independent tests upon an MS.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…The positioning bias, after applying the double-frequency ionospheric constraints, was more stable than that of the ionosphere-free combination; the positioning accuracy of BDS RTK reached 1-2 cm for the long baseline of about 100 km. Brack (2017) analysed the impact of partial ambiguity resolution (PAR) techniques on the positioning performance of dual-frequency single and combined GPS and BDS RTK for long baselines. Compared with the conventional full ambiguity resolution (FAR) schemes, the experimental results demonstrated that the time taken to reach centimetre-level positioning results was significantly reduced when using PAR techniques, especially for the combined system.…”
Section: Introductionmentioning
confidence: 99%